Structurally sophisticated 3D-printed PCL-fibrin hydrogel meniscal scaffold promotes in situ regeneration in the rabbit knee meniscus - Hebin Ma; Bowen Xie; Hongguang Chen; Lifang Hao; Haigang Jia; Dengjie Yu; Yuanbo Zhou; Puzhen Song; Yajing Li; Jing Liu; Kaitao Yu; Yantao Zhao; et al. (Materials Today Bio)
A meniscus injury is a common cartilage disease of the knee joint. Despite the availability of various methods for the treatment of meniscal injuries, the poor regenerative capacity of the meniscus often necessitates resection, leading to the accelerated progression of osteoarthritis. Advances in tissue engineering have introduced meniscal tissue engineering as a potential treatment option. In this study, we established the size of a standardized meniscal scaffold using knee Magnetic Resonance Imaging (MRI) data and created a precise Polycaprolactone (PCL) scaffold utilizing 3-Dimensional (3D) printing technology, which was then combined with Fibrin (Fib) hydrogel to form a PCL-Fib scaffold. The PCL scaffold offers superior biomechanical properties, while the Fib hydrogel creates a conducive microenvironment for cell growth, supporting chondrocyte proliferation and extracellular matrix (ECM) production. Physical and chemical characterization, biocompatibility testing, and in vivo animal experiments revealed the excellent biomechanical properties and biocompatibility of the scaffold, which enhanced in situ meniscal regeneration and reduced osteoarthritis progression. In conclusion, the integration of 3D printing technology and the Fib hydrogel provided a supportive microenvironment for chondrocyte proliferation and ECM secretion, facilitating the in situ regeneration and repair of the meniscal defect. This innovative approach presents a promising avenue for meniscal injury treatment and advances the clinical utilization of artificial meniscal grafts.